Wpływ szkoleń na podnoszenie wiedzy pracowników w zakresie systemu zarządzania jakością - Kiczek, Marek (Influence of Trainings on the Improvement of Employees Knowledge within the Scope of Quality Management, 2006)
At the end of the 1989, Poland started some political, social and economic changes that were characterized by transformation from a centrally managed and planned economy to a market economy.Nowadays, economic efficiency is the most important index in Polish companies' activity in view of market economy competitiveness.Introducing a new Quality Management System based on ISO 9000 in Polish Companies can have an impact on the increase of their competitiveness on the European Union market by the improvement of the management and the product quality.A dynamic growth of the numbers of companies, that certificate the Quality Management System based on ISO 9000, has been observed recently in Poland. Thousands firms have gained different kinds of certificates ISO so far.The aim of this article is to find the relation beetwen employees quality knowledge and the Quality Management System according to ISO 9000 efficient functioning.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 458-467